Identity negotiation strategies among Indonesian LGBT diaspora on TikTok amid digital persecution - Dwi Firli Ashari (SIMULACRA: JURNAL SOSIOLOGI, 2026)
In Indonesia, the LGBT community remains stigmatized as a threat to national culture. This hostility compels many LGBT Indonesians to migrate, yet their digital presence on platforms like TikTok continues to attract persecution from Indonesian audiences. This study examines how two Indonesian LGBT diaspora members, Kasim (@thereal_indobule, Australia) and Ragil (@ragilmahardika, Germany), negotiate their identities on TikTok and respond strategically to the digital persecution those articulations provoke. Employing critical content analysis of 70 TikTok videos and their accompanying comments, the study draws on Stuart Hall’s cultural identity theory, Ponzanesi’s digital diaspora framework, and Wijaya’s concept of digital homophobia. Findings reveal four thematic strategies of identity negotiation: performative entry and gradual disclosure, everyday domesticity and diaspora narration, familial and relational visibility, and direct audience engagement. Two counter-persecution strategies are identified: gay visibility as strategic normalization and mock impoliteness as discursive resistance. The study contributes to digital diaspora and queer media scholarship by demonstrating how TikTok functions as a contested space where marginalized identities are simultaneously performed, policed, and defended through platform-specific creative practices.